2004
DOI: 10.1074/jbc.m409205200
|View full text |Cite
|
Sign up to set email alerts
|

A Nonenzymatic Modification of the Amino-terminal Domain of Histone H3 by Bile Acid Acyl Adenylate

Abstract: Although it has been proposed that the secondary bile acids, deoxycholic acid and lithocholic acid, increase the number of aberrant crypt foci in the colon and may act as colon tumor promoters, there is little evidence detailing their mechanism of action. Histones play an important role in controlling gene expression, and the posttranslational modification of histones plays a role in regulation of intracellular signal transduction. In particular, the amino-terminal tail domain of histone H3 is sensitive to sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…However, we cannot rule out that this mark might be added to histones in a non-enzymatic process, as has been shown through investigations of different marks on proteins including histones. [28][29][30] Interestingly, in yeast we found a co-occurrence of H3S28ac and nearby H3S31ac. This S31 residue is found only on the H3 variant H3.3 in mammalian cells (which is the only sequence found in yeast), and could provide an H3 variant specific PTM, which is quite rare.…”
Section: Discussionmentioning
confidence: 92%
“…However, we cannot rule out that this mark might be added to histones in a non-enzymatic process, as has been shown through investigations of different marks on proteins including histones. [28][29][30] Interestingly, in yeast we found a co-occurrence of H3S28ac and nearby H3S31ac. This S31 residue is found only on the H3 variant H3.3 in mammalian cells (which is the only sequence found in yeast), and could provide an H3 variant specific PTM, which is quite rare.…”
Section: Discussionmentioning
confidence: 92%
“…The acyl-adenylate has an electrophilic carbonyl-carbon and spontaneously reacts with the amino group of taurine [3], substance P [5], lysozyme [5], and histone [6] in a phosphate buffer solution, indicating a higher reactivity of the acyl-adenylate toward amino group. BAs are metabolized to their acyl-glucuronides [7][8][9][10][11] and react in vitro with proteins, resulting in BA-protein adducts [12].…”
Section: Introductionmentioning
confidence: 99%
“…Finally adenylation with AMP has also been observed under in vitro conditions (24). In principle, the CoA thioester, the acyl glucuronide, or the adenylate should be capable of binding irreversibly to proteins (18,25,26). However, no detailed study on the structural analysis of protein-bound LCA formed in the liver has been reported.…”
mentioning
confidence: 98%
“…LCA acyl-adenylate (LCA-AMP) was chemically synthesized by the method previously reported (26). The synthetic products were purified by column chromatography on Sephadex LH-20 (40 3 1.5 cm ID) using 40% methanol as the eluent at a flow rate of 18 ml/h.…”
Section: Synthesis Of Lca Acyl-adenylatementioning
confidence: 99%